2018
DOI: 10.1108/tr-04-2017-0079
|View full text |Cite
|
Sign up to set email alerts
|

Tourist’s preferences in selection of local food: perception and behavior embedded model

Abstract: Purpose Locally derived foods from the lens of restaurant settings play an important source of tourist attraction. Surprisingly, research into this sector is quite scarce. The aim of the paper is to develop and empirically examine a conceptual framework on tourist’s preferences in selecting local foods. The framework includes tourists’ satisfaction, quality of food, tourist’s perception, purchase intention and purchase behavior among tourist’s selection for local foods. Design/methodology/approach The resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 90 publications
0
26
0
2
Order By: Relevance
“…A recent study on tourists' preferences in food selection in Malaysia found that tourists' behaviour and perception had a positive and significant impact on the intention of purchasing local food (Rahman, Zaman, Hassan, & Wei, 2018). The study suggests the managers and policymakers strengthen the restaurants' competitive position by identifying and understanding of tourists' behaviour and also assessing the tourists' acceptability in local foods.…”
Section: Purchase Intentionmentioning
confidence: 90%
“…A recent study on tourists' preferences in food selection in Malaysia found that tourists' behaviour and perception had a positive and significant impact on the intention of purchasing local food (Rahman, Zaman, Hassan, & Wei, 2018). The study suggests the managers and policymakers strengthen the restaurants' competitive position by identifying and understanding of tourists' behaviour and also assessing the tourists' acceptability in local foods.…”
Section: Purchase Intentionmentioning
confidence: 90%
“…According to Rahman, Zaman, Hassan, and Wei (2018), tourists should first have a positive perception of local food consumption. Visibility (social media, billboards, etc.)…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Although the results of this study are abundant, suggestions for future studies are still proposed. First, the results can be distinctive in terms of food culture (Cheung, 2009; Choe & Kim, 2019; Eves & Cheng, 2007; Peštek & Činjarević, 2014; Rahman, Zaman, Hassan, & Wei, 2018; Ruetzler, 2008; Verbeke & Poquiviqui López, 2005). Thus, future studies need to compare the results in terms of food culture and examine if the findings are similar.…”
Section: Conclusion and Suggestions For Future Studiesmentioning
confidence: 99%